Clinical outcomes and risk factors of non-curative endoscopic submucosal dissection for early gastric cancer: a retrospective multicenter study in Zhejiang, China - Jin, Chao-qiong; Zhao, Jing; Ding, Xiao-yun; Yu, Liang-liang; Ye, Guo-liang; Zhu, Xin-jian; Shen, Jian-wei; Yang, Ye; Jin, Bo; Zhang, Chun-li; Lv, Bin (Frontiers in Oncology, 2023)
Endoscopic submucosal dissection (ESD) for early gastric cancer (EGC) does not always lead to curative resection, risk factors of lymph node metastasis (LNM) /local cancer residue after noncurative ESD for EGC have not been fully elucidated; we therefore aimed to clarify them and evaluated whether "eCura system" was reliable for the risk stratification of LNM after noncurative ESD.We conducted a multicenter retrospective study at 7 institutions in Zhejiang, China, on 128 patients who underwent noncurative ESD for EGC. Patients were divided into two groups according to the therapeutic regimen after noncurative ESD. We analyzed the risk factors for LNM, local cancer residue, cancer recurrence and cancer-specific mortality. Furthermore, outcomes in each risk category were also compared after applying the "eCura system".Among 68 patients undergoing additional surgery group, LNM was found in 3(4.41%) patients while local cancer residue was found in 8(11.76%) patients. Multivariate analysis showed that upper third location and deep submucosal invasion were independent risk factors of LNM and local cancer residue.Among 60 patients who underwent simple follow-up, local cancer recurrence was found in 4 (6.67%) patients and cancer-specific mortality was found in 1(1.67%) patients. There were no independent risk factor of cancer recurrence and cancer-specific mortality in our study. During the follow-up period, 5-year overall survival (OS) and disease-free survival (DFS) were 93.8% and 88.9%. Additionally, LNM and cancer recurrence were significantly associated with the eCura scoring system (P=0.044, P=0.017), while local cancer residue and cancer-specific mortality were not (P=0.478, P=0.131).Clinicians should be aware of the risk factors for prognosis of patients with noncurative ESD to determine subsequent treatment. Through the application of "eCura system", additional surgery should be performed in intermediate/high-risk in LNM.